Factors associated with the performance level in the independent student work of La Salle University optometry program - Figueroa Olarte, Luisa Fernanda (Universidad de La Salle. Revistas. Ciencia y Tecnología para la Salud Visual y Ocular., 2009)
This research project formed a part of the macro project “Pedagogic Practices in the topic of methodologies and the resources of learning “in general terms it was made in order to realize of the actions and reflections daily developed in the classroom, to allow a major comprehension of the pedagogic exercise from the methodological up to the evaluation. Objective: To identify and to describe the factors associated with the level of performance in independent work of the students of the Optometry program of La Salle University. Methodology: We made qualitative research of descriptive character. It is also educational research since there is directed to obtain information of the educational processes and to improve the practice. The compilation of information fulfilled with seven focal groups and thirteen interviews to teachers and students of the different semesters of the program. Results: it was possible to identify that teachers and students have clear the concepts of presencial and independent time, but they have confusion about the hours of dedication for every activity according to the study plan, the syllabus its planned without any type of participation of the student, and the evaluation is especially of “confirmatory” character by means of questions in quizes and partial. In the accomplishment of independent time on the part of the students, was recognized the influence of such aspects as: motivation, time of dedication, family, type of task, place of accomplishment, evaluation and the different forms of planning. Conclusions: The concept that teachers and students have about the credit system is good, but it does not seem to be clear how many hours they have to dedicate in presencial and independent time according to the program. The qualification would be the principal motivation at the moment of realizing the tasks, especially in the first semesters, and it seems to have basically a “confirmatory” character. The student has major commitment with academic spaces related directly to their future professional occupation. Factors as family, type of task, place, company and work also are important to consider and take into account about the performance of the students in their independent work.